(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-3-81-96 The article is devoted to the relevant problems of modern communicative linguistics and network genre studies. A comparative analysis of dialogic communication in live speech with dialogic communication on the Internet (within the framework of information and commentary blocks) was carried out according to the following criteria: 1) pragmatic coordinates of communication; 2) the type of dialogue according to the nature of the addressee; 3) the main factors influencing the organization of dialogic structures; 4) thematic specificity of the dialogues. Online comments is characterized as a response Internet genre, the texts of which are thematically, structurally-semantically and pragmatically closely related to the original (root) message (post) and form a kind of dialogic unity with it. The studied network genre meets the urgent need of Internet users for feedback and is a time-demanded media embodiment of the addressee factor. This genre is intended primarily to express the point of view of the addressee and various modal meanings of the sphere associated with the addressee: agreement or disagreement, approval or disapproval, various cognitive-modal assessments and qualifications. Key words: Internet communication, online comments, information and commentary block, dialogism, dialogical relations, casual dialogue, Internet dialogue